4CPS-018 Specialist pharmacist-led support in primary care to optimise cardiovascular risk management in patients with atrial fibrillation (af-patients). (2nd March 2018) - Durand, L; Chahal, J; Shabana, A; Singh, H; Earley, M; Saja, K; Antoniou, S
Abstract : Background: Patients with atrial fibrillation (AF) are at high risk of serious cardiovascular complications such as stroke. Oral anticoagulation is an effective prevention but the rate of appropriate anticoagulation remains suboptimal in England. A London CCG initiated an AF-improvement scheme in 2017: a specialist cardiovascular pharmacist in secondary care led on clinically supporting general practitioners (GPs) in optimising the management of AF-patients. Purpose: To assess the impact of a specialist pharmacist on improvement of anticoagulation in AF-registered patients. Material and methods: Over 4 months a specialist pharmacist reviewed 20 GPs' electronic systems (Emis ® ) using an electronic program (APL-tool ® ) to extract and select global and individual patients' data to assess for anticoagulation. Patients without anticoagulant/on antiplatelet monotherapy were listed in four categories: Anticoagulation to be initiated. Multidisciplinary team (MDT) referral for complex patients to decide about anticoagulation. Contra–indication for anticoagulation. Anticoagulation not indicated i.e. CHA2DS2–VASc=0. The pharmacist reviewed every clinical record for confirmation of AF, patient's characteristics and blood results. Based on national guidelines, eligible AF-patients were initiated either on a direct oral anticoagulant (DOAC) or warfarin. The primary endpoint was the difference in the percentage of anticoagulated patients before and after intervention (McNemar test). The secondary endpoints include type of pharmacist's intervention, number and types of exceptions/referrals to community pharmacists and patients' refusal (all presented in final results). Results: 1315 AF-registered patients were reviewed, of which 814 patients (62%) were anticoagulated at baseline. Following pharmacist intervention, 501 patients were identified as not receiving anticoagulation, and were assessed into the following categories: 283 patients (57%). 70 patients (14%). 82 patients (16%). 66 patients (13%). GPs agreed with 100% of the pharmacists' decisions for anticoagulation. So far, 241 new patients from category 1 and 2 are now on appropriate anticoagulation, leading to an interim improvement of 18% (62 to 80%, p<0, 0001). Eleven patients declined anticoagulation. Conclusion: Our interim results highlight the benefit of a specialist pharmacist working in GP practices with increases of anticoagulation among AF-patients. This is an innovative example of working across traditional boundaries between primary and secondary care, with an integrated and patient-centred approach. Future developments includes GP educational tools to facilitate initiating anticoagulation and integration of community pharmacists to support patients' adherence. No conflict of interest